Design and Development of an LNB based DVB-S receiver - H, Mahmudul; M, Sirajum; N.S, Syed; K.M. F.H, A; H, Shahina; I.R, Tasnim (International Journal of Engineering and Technology, 2018)
Â This paper introduces an LNB-based DVB-S receiver with respect to sync byte detection. The basic configuration of DVB-S for decoding is the major focus of this work, where the main task is to decode the received signal from the satellite with a good SNR. Sync-byte detection is one of the challenges of receiver design. An algorithm is developed to overcome the problems associated with Sync-byte detection which can efficiently perform Sync-byte detection. After decoding the signal, the SNR is found to be 9.62 dB, which represents quiet a good signal. A channel list is identified in the final result.Â Â